Exploring Qur’anic Coherence Through Salwa El-Awa’s Pragmatic Framework - Nisa', Mir'atun; Mustaqim, Abdul; Sahiron, Sahiron (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2024)
This study examines Salwa El-Awa's pragmatic approach to the structural and thematic coherence of the Qur’an, as outlined in her work Textual Relations in the Qur’an: Relevance, Coherence, and Structure. Employing a qualitative and descriptive-analytical methodology, this research explores the theories of coherence and relevance to understand the role of paragraph markers in establishing thematic and structural relationships between verses. The analysis focuses on two chapters, Surah al-Ahzab and Surah al-Qiyamah, to identify how these markers delineate paragraph boundaries and ensure the relevance of verses to the overarching message. The findings reveal that Salwa El-Awa's approach surpasses classical methods such as munasabah, which are limited to linear connections between verses, and addresses the shortcomings of modern approaches that often overlook the thematic relevance of textual components. Paragraph markers identified by Salwa elucidate structural relationships within the chapters, even when verses appear thematically unrelated. Furthermore, this study underscores the importance of integrating the internal textual context of the Qur’an with historical, social, and cultural dimensions to enhance interpretive depth.